Johannes Bugenhagen : Selected Writings, Volume 1 and Volume II - Hendel, Kurt K.; Hendel, Kurt K. (Book collections on Project MUSE., 2015)
Martin Luther did not reform the church by himself. Throughout his life, and in the decades after it, many others spent their careers and risked their lives in the pursuit of a renewed church. They, too, made crucial contributions to the Wittenberg reform movement. In this landmark set, an extensive collection of writings from Johannes Bugenhagen, Luther's pastor, friend, and colleague in reform, are presented for the first time in English. The vast majority of these works have only been available in their original, sixteenth-century editions. Called by some the Second Apostle to the North, Johannes Bugenhagen (1485-1558) was a pivotal figure in the organization of the Lutheran movement in northern Germany and in parts of Scandinavia. His writings and diverse reforming activity made a lasting impression on church administration, education, the care of the poor, worship, and theology. Representing the fruit of many years of labor, Reformation scholar Kurt K. Hendel has organized this extensive collection thematically-introducing us to Bugenhagen the man, the theologian, the exegete, the pastor, the church organizer, and the social reformer.